Dampak Perkuliahan Daring Terhadap Penguasaan Keterampilan Renang Gaya Bebas - Gilar, Muhamad Fajar; Nugraha, Eka; Nuryadi, Nuryadi (STAMINA, 2024)
The Covid-19 pandemic has forced the learning system on campus to change drastically from face-to-face meetings to courageous learning. The phenomena found in the field show that it is more difficult for students to understand the aquatic learning material provided by educators, the lack of interaction between educators and students makes it difficult for them to understand the aquatic learning materials provided, students find it more difficult to ask about aquatic learning materials that they do not understand and lack of student concentration when done brave learning. The purpose of this study was to determine the differences in the freestyle swimming skills of PJKR undergraduate students during offline learning. The research method uses a quantitative method with an ex-post facto design by collecting data by observation and testing. The results of this study indicate that there is a significant difference. This states that if the sig. (2-tailed) < 0.05 so that it can be interpreted that there is a significant difference in freestyle swimming skills when daring and alluring. when brave shows a value of 2.63 while offline shows a value of 2.97 so that the freestyle swimming skills when lure are better than when brave.